2015
DOI: 10.1002/chem.201503661
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin Metalation at MgO Surfaces: A Spectroscopic and Quantum Mechanical Study on Complementary Model Systems

Abstract: We show that both single-crystalline and nanostructured MgO surfaces convert free-base tetraphenyl porphyrin (2HTPP) into magnesium tetraphenyl porphyrin (MgTPP) at room temperature. The reaction can be viewed as an ion exchange between the two aminic protons of the 2HTPP molecule with a Mg(2+) ion from the surface. The driving force for the reaction is the strong stability of the formed hydroxyl groups along the steps and at defects on the MgO surface. We have used an integrated characterization approach that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
77
1
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(94 citation statements)
references
References 31 publications
7
77
1
9
Order By: Relevance
“…29 We assume that the Consequently, a significantly higher surface fraction is available for the physisorption of the free base on larger cubes, which seems to take place at extended (100) terraces. This is consistent with our observation that on the large MgO cubes only a minor fraction of the adsorbed porphyrin is metalated whereas the majority exists as the free base.…”
Section: Discussionmentioning
confidence: 99%
“…29 We assume that the Consequently, a significantly higher surface fraction is available for the physisorption of the free base on larger cubes, which seems to take place at extended (100) terraces. This is consistent with our observation that on the large MgO cubes only a minor fraction of the adsorbed porphyrin is metalated whereas the majority exists as the free base.…”
Section: Discussionmentioning
confidence: 99%
“…In that work we have shown that the low‐coordinated surface cations at edge and corner sites of the MgO nanocubes play an important role for the reactivity towards the porphyrin film. We have shown that the low coordinated Mg 2+ ions are the key species in porphyrin metalation ,. We could demonstrate that 2H‐TPP adsorbs in a flat‐lying orientation on the nanocubes, limiting the amount of porphyrin that is bound per cube.…”
Section: Introductionmentioning
confidence: 88%
“…In our recent work we investigated the anchoring of organic films to oxide surfaces combining surface science work and studies on well‐defined oxide nanoparticles . Among the most commonly used linkers for oxides is the carboxylic acid group .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these reactions either the two aminic protons in the central cavity of the molecule are exchanged by a metal ion from solution (metalation) or vice versa (demetalation), or the metal center of a metalloporphyrin is exchanged by another metal ion (metal center exchange). A significant number of studies also exists addressing metalation of porphyrins on surfaces under ultrahigh vacuum with codeposited metal atoms, substrate metal atoms, oxide lattice ions, and recently also coordination of ions from aqueous solution . However, to our knowledge, the work of Doyle et al., showing the exchange of nickel metal centers with copper substrate atoms, is the only available study on metal center exchange of adsorbed porphyrins under ultrahigh vacuum.…”
Section: Introductionmentioning
confidence: 99%